(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
As urban areas account for over 70% of global carbon dioxide emissions, integrated transport planning has emerged as a critical mechanism for achieving low-emission urban mobility. This study examines the integration of land use and transportation planning as a strategy for sustainable mobility through a descriptive case study analysis of four major U.S. cities: New York City, San Francisco, Boston, and Los Angeles. The findings demonstrate a clear correlation between compact cities and sustainable modal shares. Compact cities such as New York City, San Francisco, and Boston successfully leverage high public transit modal shares to drive down per capita emissions. In contrast, sprawling metropolitan areas like Los Angeles remain heavily car-dependent. The findings also support existing discourse on sustainable urban mobility that city-wide electrification alone will not achieve the required long-term climate obligations, but rather depends on an interplay of compact city design, boosting public transit use, and accelerating the adoption of electric vehicles. Thus, this study proposes the ABC roadmap as a long-term strategy for cities to achieve their respective climate change obligations